Emergency Department and Intensive Care Unit Overcrowding and Ventilator Shortages in US Hospitals During the COVID-19 Pandemic, 2020-2021. (July 2022) - Sandhu, Paramjit; Shah, Ami B.; Ahmad, Farida B.; Kerr, Justin; Demeke, Hanna B.; Graeden, Ellie; Marks, Suzanne; Clark, Hollie; Bombard, Jennifer M.; Bolduc, Michele; Hatfield-Timajchy, Kendra; Tindall, Erica; et al.
Objective: In 2020, the COVID-19 pandemic overburdened the US health care system because of extended and unprecedented patient surges and supply shortages in hospitals. We investigated the extent to which several US hospitals experienced emergency department (ED) and intensive care unit (ICU) overcrowding and ventilator shortages during the COVID-19 pandemic. Methods: We analyzed Health Pulse data to assess the extent to which US hospitals reported alerts when experiencing ED overcrowding, ICU overcrowding, and ventilator shortages from March 7, 2020, through April 30, 2021. Results: Of 625 participating hospitals in 29 states, 393 (63%) reported at least 1 hospital alert during the study period: 246 (63%) reported ED overcrowding, 239 (61%) reported ICU overcrowding, and 48 (12%) reported ventilator shortages. The number of alerts for overcrowding in EDs and ICUs increased as the number of COVID-19 cases surged. Conclusions: Timely assessment and communication about critical factors such as ED and ICU overcrowding and ventilator shortages during public health emergencies can guide public health response efforts in supporting federal, state, and local public health agencies.